1993
DOI: 10.1093/oxfordjournals.humrep.a138048
|View full text |Cite
|
Sign up to set email alerts
|

The techniques and complications of out-patient uterine washing in the assessment of endometrial function

Abstract: The complications of a consecutive series of 90 uterine washings performed among 52 women were studied. The amount of discomfort was significantly less than that of endometrial biopsy but greater than that of cervical smear or blood sampling. Incomplete recovery of fluid (< 8 ml from 10 ml flushing fluid) was reported in only 3% of cases. Vaginal bleeding, pelvic infection and delayed abdominal pain were not encountered. The techniques of uterine washing are simple and may have important implications in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…EL was performed by injecting 2 mL of normal saline into the uterine cavity via a sterile hysterosalpingogram catheter (Lyco, San Antonio, TX) and recovered by suction. Flushing was performed with fresh saline up to 5 times to obtain a minimum of 4 mL of EL fluid [9]. VL and EL specimens were centrifuged at 200×g for 10 min, and supernatants were frozen at −70°C.…”
Section: Methodsmentioning
confidence: 99%
“…EL was performed by injecting 2 mL of normal saline into the uterine cavity via a sterile hysterosalpingogram catheter (Lyco, San Antonio, TX) and recovered by suction. Flushing was performed with fresh saline up to 5 times to obtain a minimum of 4 mL of EL fluid [9]. VL and EL specimens were centrifuged at 200×g for 10 min, and supernatants were frozen at −70°C.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial cytological samples may be obtained by three methods: washing, by aspiration and using endometrial brushes. Devices used to obtain endometrial samples include the Gravlee Jet Wash (Becton Dickinson, AG, Basel, Switzerland) 112 , the Endocyte system (Laboratoire CCD, Paris, France) 113 , the Endo–Pap instrument (Sherwood Medical Laboratories, St Louis, Missouri, USA) 114–116 , the Endoscann or Gynoscann (Pedema, AG, 6300 Zug, Switzerland) 15,117–119 , the Isaacs sampler (Kendall Research Center, Barrington, Illinois, USA) 120 , the Vakutage (Warner‐Chilcott, Moms Plains, New Jersey, USA) 121 , the MiMark endometrial cell sampler (Simpson‐Boyse Inc, Baltimore, Maryland, USA) 122 , paediatric Foley catheters 123 , and the Pipelle de Cornier aspiration device 124 . The Vakutage system detects 93% of endometrial malignancies and 89% of endometrial hyperplasias 121 .…”
Section: Effects Of Hormone Replacement Therapy On the Endometriummentioning
confidence: 99%
“…8,10,28 This technique can be applied during the window of implantation without disrupting the implantation process, 8,10,28 and is associated with less discomfort than endometrial suction microbiopsy. 9 Moreover, a single aspiration sample from 1 cm above the internal os and a single tissue biopsy was previously observed in hysterectomy specimens to be representative of other areas sampled within the uterine cavity (H. Beier, pers. comm.).…”
Section: Discussionmentioning
confidence: 95%
“…Aspiration and flushing of the endometrial cavity in the peri-implantation period of menstrual cycles has been performed without detrimental effect on pregnancy rates. [8][9][10] Analysis of endometrial secretions showed proteins originating from transudate of serum, leakage products of apoptotic epithelial cells, and glandular secretion. 11 The composition of the secretions varies during the menstrual cycle as a result of changing ovarian steroid levels.…”
Section: Introductionmentioning
confidence: 99%